(untitled) - Food and Agriculture Organization of the United Nations (Rome, 2005)
The objective of the World Programme for the Census of Agriculture 2010 is to assist countries in the conduct of their national census of agriculture. This publication provides a detailed list of items suitable for inclusion in the national agricultural census programme as well as definitions, concepts and standards to be adopted.
Keywords: Agriculture,Nông nghiệp; Statistics,Thống kê